Dynamics of dissolved inorganic carbon in the South China Sea: A modeling study. (July 2020) - Du, Chuanjun; Gan, Jianping; Hui, Chiwing Rex; Lu, Zhongming; Zhao, Xiaozheng; Roberts, Elliott; Dai, Minhan
Highlights: DIC in the SCS is modulated by intrinsic dynamics and extrinsic exchanges via straits. 3D-DIC transports across straits and within the SCS are examined. DIC inventory in euphotic zone decreased in spring/summer but increased in fall/winter. Abstract: Using a validated, three-dimensional, coupled physical-biogeochemical model, this study examines the dynamics of dissolved inorganic carbon (DIC) in the South China Sea (SCS). The model identifies characteristic differences in DIC concentrations between the SCS and adjacent West Philippine Sea (WPS), showing an increase in DIC of up to 140 μmol kg −1 in the upper 2000 m layer from the WPS to the vicinity of the northern SCS. This increasing pattern continues from the northern to the southern SCS, but to a much lower degree (<20 μmol kg −1 increase). Overall, spatial and seasonal variation of DIC in the SCS are evidently modulated by both intrinsic dynamics (e.g., river plumes, vertical mixing, basin-scale upwelling and eddies), and extrinsic exchanges via various straits. The inputs of DIC to the SCS are mainly through the Luzon Strait in the upper layer (depth, h  < 600 m) and from the deep WPS at > 1600 m. Exports of DIC occur through other straits and the SCS intermediate water outflow (600 m to 1600 m) via the Luzon Strait. The model shows upward transport of DIC in the upper 400 m and below 1100 m, in contrast to downward DIC transport between 400 m and 1100 m. Seasonally, both DIC concentrations and fluxes in the upper layer have larger dynamic ranges in winter than in summer, attributable to the combined effects of enhanced Kuroshio intrusion, stronger vertical upwelling and greater biogeochemical alterations. A balance of various constitutive DIC terms revealed that horizontal and vertical advection is an order of magnitude greater than the other terms of the DIC budget, which has an opposite sign and thus tends to neutralize each other. The model indicated a decrease in the DIC inventory in the euphotic zone in spring and summer caused by net DIC consumption, and a contrasting increase in fall and winter primarily influenced by DIC vertical transport. In intermediate and deep layers, physical transport processes play a dominant role in the seasonal variation of DIC inventories. In the upper 150 m, DIC fluxes and their stoichiometry with nutrient fluxes, which potentially impact the air-sea CO2 fluxes, are largely driven by excess vertical DIC fluxes compared to horizontal fluxes via the Luzon Strait.